Do creative industries enhance employment growth? Regional evidence from Colombia - Mercedes Campi; Marco Due\~nas; Tommaso Ciarli (Inter-American Development Bank (IDB), 2022)
Do creative industries have positive spillovers for the local economy in middle-income countries, for instance by attracting creative workers who benefit entrepreneurs and workers in other industries? Creative industries are considered highly innovative and productive and several studies in high-income countries have revealed such spillovers. However, the institutional and economic settings in middle-income countries may not be as conducive to them. Creative industries represented between 2.7 and 3.3 percent of Colombian employment in 2008 and 2017. Using granular employment data, we study their agglomeration patterns between 2008 and 2017. We find agglomeration in the largest cities (Bogota, Medelln, and Cartagena) and in a few smaller cities. Using methodologies from prior studies yields a positive relationship between creative industry agglomeration and employment in non-creative services industries. However, after controlling for endogeneity using a shift-share instrumental variable approach, we find, contrary to analyses of high-income countries, no significant impact of an increase of creative industries employment on employment growth in other industries.
Keywords: Z18; O00; D62; 330; creative industries; agglomerations; relatedness; employment growth; Colombia